2022
DOI: 10.3390/plants11070897
|View full text |Cite
|
Sign up to set email alerts
|

Hoop House and Field Evaluation of Tigernut (Cyperus esculentus L. var. sativus Boeck) Selections in New Jersey, USA

Abstract: Tigernut or ‘chufa’ (Cyperus esculentus L. var. sativus) is gaining popularity in the United States as a high energy tuber crop known for sweet and chewy taste, 40–45% gluten-free digestible carbohydrate, high dietary fiber content, healthful fatty acid profile (73% monounsaturated, 18% saturated, 9% polyunsaturated—similar to olive oil), high oleic acid, and high P, K, and vitamins C. E. Tigernut tubers were obtained from specialty crop markets in central NJ and purchased online from commercial distributors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
4
2
Order By: Relevance
“…Conversely, the individual tuber weight in our study was significantly lower compared to the data from Ayeni et al (68–78.6 g) [ 30 ]. The oil content reported by Ayeni et al (20.0–26.4%) was comparable to our findings, while the protein content was higher (6.4–8.1%) [ 30 ].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Conversely, the individual tuber weight in our study was significantly lower compared to the data from Ayeni et al (68–78.6 g) [ 30 ]. The oil content reported by Ayeni et al (20.0–26.4%) was comparable to our findings, while the protein content was higher (6.4–8.1%) [ 30 ].…”
Section: Discussioncontrasting
confidence: 98%
“…The plant heights recorded by Ayeni et al ranged from 91 to 111 cm, which was higher than the values observed in our study. The minimum and maximum number of tubers in our research were higher compared to the data gathered by Ayeni et al [30]. Conversely, the individual tuber weight in our study was significantly lower compared to the data from Ayeni et al (68-78.6 g) [30].…”
Section: Discussioncontrasting
confidence: 84%
“…, is indigenous to the Mediterranean region of Africa ( Follak et al., 2016 ). It is widely distributed in many northern temperate regions and is becoming increasingly popular as an energy crop in China, India, Egypt, and the United States ( Ayeni, 2022 ). C. esculentus possesses exceptional traits, such as drought resistance and salinity tolerance ( Duan et al., 2022 ; Zhang et al., 2023 ; Zhu et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to select crops that are more suitable for both forage yield, grain and oil supply under water shortage conditions to improve livestock production and may alleviate food crisis in arid and semi-arid areas. Meanwhile, the Cyperus esculentus is a grass like plant widely distributed in many northern temperate regions and is gaining popularity in China, India, Egypt and the United States as an energy crop (Arafat et al, 2009;Bamishaiye et al, 2010;De Castro et al, 2015;Ayeni, 2022). Its aboveground parts (leaves) are used as forage, and its belowground parts are edible tubers with sweet taste with high levels of protein, fatty acids and starch, that make it a potential alternative to wheat and soybeans in many countries (Sańchez-Zapata et al, 2012;Ahmed and Hussein, 2014;Codina-Torrella et al, 2015;Ayeni, 2022).…”
mentioning
confidence: 99%
“…Meanwhile, the Cyperus esculentus is a grass like plant widely distributed in many northern temperate regions and is gaining popularity in China, India, Egypt and the United States as an energy crop (Arafat et al, 2009;Bamishaiye et al, 2010;De Castro et al, 2015;Ayeni, 2022). Its aboveground parts (leaves) are used as forage, and its belowground parts are edible tubers with sweet taste with high levels of protein, fatty acids and starch, that make it a potential alternative to wheat and soybeans in many countries (Sańchez-Zapata et al, 2012;Ahmed and Hussein, 2014;Codina-Torrella et al, 2015;Ayeni, 2022). However, to our best knowledge, there is a little information on the nutritive value of the above-and under-ground parts of C. esculentus in respond to different planting modes (CC vs RC) and initial mowing time, even though it has been cultivated for many years in the desert oasis transition zone (Tan et al, 2022;Zhang et al, 2022).…”
mentioning
confidence: 99%